Lawn Mower – An Automated Machine (International Journal of Innovative Research in Computer Science & Technology, 2020)
Robotics is a branch of engineering that  combines more than one area of research and is used to  design machines that helps us to assist in our day- to-day  life. There are various inventions existing that are  created using robotics and lawn mower is one such  inventions. Lawn Mower or lawn cutter is a mechanical  device whose work is to cut grass in our lawns. The  automated lawn mower is used to do the same task  automatically with help of different sensors and  electrical components. This review aims to evaluate the  technology that has been not used still to make the  system more advanced. This paper presents the currently  based system and techniques and retouches the areas that  need to be modified for better performance.
Keywords: Robotics; Lawn Mower; sensors; electric components